PENGARUH KUALITAS PRODUK, BRAND IMAGE TERHADAP LOYALITAS DENGAN KEPUASAN SEBAGAI VARIABEL INTERVENING - Damayanti, Cintya; Wahyono, Wahyono (Management Analysis Journal, 2015)
__________________________________________________________________________ The purpose of this research is to know the influence of Product Quality to theÂ  Satisfaction, the influence of Brand image to the Satisfaction, the influence of Product Quality to the Customersâ Loyality, the influence of Brand image to the Customersâ Loyality, the influence of Customersâ Satisfaction to the Customersâ Loyality, the influence of Product Quality to theÂ  Customersâ Loyality by Customersâ Satisfaction, and the influence of Brand image to the Customersâ Loyality by Customersâ Satisfaction. The population of this research is the customers who consume instant noodle Supermi. The samples have been taken in this study is not known for certain. The technique of this research uses iteration formula. The methods of collecting data are quesioner. The analysis methods are path analysis. The result of this research is retrieved two equation path analysis, It shows us that Product Quality and Brand image influence the Customersâ Loyality directly and indirectly by the Satisfaction. The conclusion of this research is the Product Quality and Brand image influence directly and indirectly increasing Loyality by Satisfaction.